NETWORKING 2012 11th International IFIP TC 6 Networking Conference, Prague, Czech Republic, May 21-25, 2012, Proceedings, Part II - Bestak, Robert; Kencl, Lukas; Li, Li Erran; Widmer, Joerg; Yin, Hao.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The two-volume set LNCS 7289 and 7290 constitutes the refereed proceedings of the 11th International IFIP TC 6 Networking Conference held in Prague, Czech Republic, in May 2012. The 64 revised full papers presented were carefully reviewed and selected from a total of 225 submissions. The papers feature innovative research in the areas of network architecture, applications and services, next generation Internet, wireless and sensor networks, and network science. The second volume includes 32 papers and is organized in topical sections on video streaming, peer to peer, interdomain, security, cooperation and collaboration, DTN and wireless sensor networks, and wireless networks.
Keywords: Computer science; Computer Communication Networks; Software engineering; Data encryption (Computer science).; Computer software; Information Systems; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Algorithm Analysis and Problem Complexity; Software Engineering; Management of Computing and Information Systems; Data Encryption